Identifying joint-specific limitations and targets for improving weightlifting performance - Kipp, K. (ISBS Proceedings Archive (Michigan), 2021)
The purpose of this study was to determine the relative effort (RE) of the extensor and plantarflexor muscles during the pull phase of the clean. Five weightlifters performed the clean at 85% of their one-repetition maximum while motion capture and ground reaction forces were recorded and used to calculate lower body net joint moments via inverse dynamics (NJMID). Joint angle and angular velocity data were used as input to a musculoskeletal model that estimated maximum NJM (NJMmax) weightlifters could theoretically generate. The RE of the hip and knee extensor and ankle plantarflexor muscles were calculated as the ratios between NJMID and NJMmax. The results suggest that the knee extensor muscles operate close to max capacity during both pull phases, and that the plantarflexor muscles operate close to their max capacity during the second pull.